STIMULATION OF REPARATIVE OSTEOGENESIS IN PSEUDOARTHROSIS IN THE EXPERIMENTAL AND CLINICAL STUDY - V. A. Shilin; A. A. Safronov (Креативная хирургия и онкология)
The article represents the results of investigation of reparative osteogenesis with using of composite material “LitAr” in the zone of pseudoarthrosis of long bones.